Health-related factors leading to disabilities in Korea: Survival analysis - Kim, TaeEung; Park, So-Youn; Oh, In-Hwan (Frontiers in Public Health, 2022)
The purpose of this study is to analyze (a) population and socioeconomic factors affecting disability, excluding the occurrence of disability due to accidents and congenital diseases, and (b) health-related behavioral factors and factors that can prevent and reduce the cause of disability due to disease in Korea. This study was a longitudinal research. Data were obtained from The 2018 Korean Health Panel (KHP) is a survey jointly conducted by the Korea Institute of Health and Social Affairs and the National Health Insurance Service. A total of 7, 372 (Mage = 52.14, SD = 21.39; Male = 47.52%) were analyzed in this study. People with Higher education attainments and more income levels were associated with lower hazard of developing new disabilities (all p < 0.05). In this study, the health factors that could be related to the occurrence of new disabilities were smoking, alcohol consumption, physical activity, and stress (all p < 0.0001). However, physical activity was negatively associated with the risk of developing a disability at all follow-ups (p < 0.05). Higher scores on the number of chronic diseases (valid scores = 0, 1, 2, 3, or more) represented a greater level of newly developing disability present at all follow-ups (all p < 0.0001). This longitudinal study confirmed the relationship between health-related factors and specific chronic diseases. Its findings can be used as a crucial foundation for establishing healthcare policies and services that can lower and prevent disability by preventing and reducing specific negative health behaviors and unhealthy behavioral factors, and alleviating chronic diseases in Korea.